(untitled) (Archaeologia Adriatica, 2025)
Ceramic material is a common – and often the most frequent – find type at archaeological sites. Numerous potsherds are a typical result of archaeological excavations at sites dating from the Neolithic period onwards. However, at sites dating from the Middle Ages, pottery can become an exceptional find at church graveyards; due to often intensive historical burial activities it is generally deprived of its original contexts. Nevertheless, it may be assumed that continuous interments will not necessarily result in a displacement of the material over greater distances and it follows that the concentration of potsherds in a specific location may yet be an indication of the area, intensity and type of activity over a certain period. Hence, their presence, specific technological, typological and chronological features, frequency and distribution can expand our insight into the ways in which a researched location was used. Accordingly, this paper is dedicated to considering the informative potential of pottery finds recovered around the Church of the Assumption of the Blessed Virgin Mary in the village of Gora, located approximately eight kilometres southwest of Petrinja, mainly not in their original contexts and mostly found in the backfills of the numerous graves excavated there. The collected ceramic material has been typologically-chronologically determined based on an analysis of production-technology characteristics and preserved typological features. In accordance with the defined chronological attribution, an analysis of patterns of its occurrence, frequency and distribution at the site was carried out in a GIS environment. This opened the possibility of making specific assumptions and conclusions about patterns of use of the location over different periods.